2017
DOI: 10.3389/fpsyt.2017.00138
|View full text |Cite
|
Sign up to set email alerts
|

The Screen for Child Anxiety-Related Emotional Disorders Is Sensitive but Not Specific in Identifying Anxiety in Children with High-Functioning Autism Spectrum Disorder: A Pilot Comparison to the Achenbach System of Empirically Based Assessment Scales

Abstract: Validated brief screening instruments are needed to improve the detection of anxiety disorders in autism spectrum disorder (ASD). The Screen for Child Anxiety-Related Emotional Disorders (SCARED), a 41-item parent- and self-reported scale measuring anxiety, was compared to the Achenbach System of Empirically Based Assessment (ASEBA) scales. One hundred participants with a clinical diagnosis of high-functioning ASD, aged 8–18 years, and their parents completed the above scales. We hypothesized that the SCARED w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
2
18
0
2
Order By: Relevance
“…Current and prior data, however, show acceptable internal consistency of the modified measure [Keefer et al, 2016], and the IUS-P has been utilized in multiple studies of youth with ASD [Boulter et al, 2014;Chamberlain et al, 2013;Neil et al, 2016]. The SCARED has been used in prior studies of children with ASD [e.g., Blakeley-Smith, Reaven, Ridge, & Hepburn, 2012;Lohr et al, 2017;Stern, Gadgil, Blakeley-Smith, Reaven, & Hepburn, 2014]; however, there are concerns about children's' ability to selfreport and the specificity of anxiety screening measures with this population [Kerns et al, 2015]. It is also possible that there may be some measurement overlap between the IUS and SCARED; however, an item level comparison revealed that the SCARED included anxiety-specific symptoms of physiological arousal, somatic symptoms, and avoidance/refusal of specific situations (e.g., school) that were not included in the IUS.…”
Section: Discussionmentioning
confidence: 99%
“…Current and prior data, however, show acceptable internal consistency of the modified measure [Keefer et al, 2016], and the IUS-P has been utilized in multiple studies of youth with ASD [Boulter et al, 2014;Chamberlain et al, 2013;Neil et al, 2016]. The SCARED has been used in prior studies of children with ASD [e.g., Blakeley-Smith, Reaven, Ridge, & Hepburn, 2012;Lohr et al, 2017;Stern, Gadgil, Blakeley-Smith, Reaven, & Hepburn, 2014]; however, there are concerns about children's' ability to selfreport and the specificity of anxiety screening measures with this population [Kerns et al, 2015]. It is also possible that there may be some measurement overlap between the IUS and SCARED; however, an item level comparison revealed that the SCARED included anxiety-specific symptoms of physiological arousal, somatic symptoms, and avoidance/refusal of specific situations (e.g., school) that were not included in the IUS.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestra cohorte excluyó niños portadores de una enfermedad cromosómica, malformación o daño cerebral severo conocido e incluyó niños con lenguaje (al menos una palabra o gesto con significado), por ello creemos que se seleccionó un subgrupo de TEA con mayores habilidades cognitivas, definidos como TEA de alto funcionamiento (TEA-AF) 10,11 . A pesar que el criterio de ingreso fue entre 36 meses a 10 años, creemos que la edad al diagnóstico de TEA-AF es mayor a la población general de TEA reportada por Nassar y Daniels 12,13 y mayor a los 18-24 meses recomendados para el tamizaje de M-CHAT 14 .…”
Section: Discussionunclassified
“…La evaluación neuropsicológica consistió en medición de la conducta adaptativa y cognitiva con el test de Vineland (Vineland Adaptative Behavior Scales Survey Form: 1-100), Kaufman Brief Intelligence (K-BIT), que provee Coeficiente intelectual (CI) (M = 100, SD = 15), para CI total, verbal y no verbal y Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV), aplicable a niños y adolescentes de edades comprendidas entre 6 años 0 meses y 16 años 11 meses, que también arrojan CI de los mismos tipos descritos anteriormente 10 .…”
Section: Pacientes Y Métodounclassified
“…There may be concomitant problems such as nervousness, aggression and hyperactivity (Lecavalier, 2006;. Although the relationship of these problems with the defined features of the ASD is not entirely clear, they may complicate the clinical picture and contribute to the overall disability of the disorder (Lohr et al, 2017;Postorino et al, 2017).…”
Section: Discussionmentioning
confidence: 99%